Essentials of Functional Whole-of-Government Monitoring and Evaluation Systems: The Zambian Case - Kanyamuna, Vincent; Simui, Francis; Mubita, Aurick; Musanda, Paul (Advances in Social Sciences Research Journal, 2024)
Since the turn of the 21st century in the year 2000, it has become increasingly impossible to design and implement a development intervention, be it a project, programme or policy without articulating a sound monitoring and evaluation framework. More demanded are functional monitoring and evaluation (M&E) systems. It is for that reason that governments, civil society organisations, non-governmental organizations, bilateral and multilateral agencies have all adopted the agenda of strengthening their systems for M&E. Among others, known benefits from implementing sound M&E include enhancing accountability, feedback and learning. This paper articulates essentials development agencies, and their respective stakeholders need to put in place for their M&E systems to function well. More so, focus is on building stronger whole-of-government M&E systems. Essentially, a typical M&E system would have two sides, both of which would be crucial for a successful and functional whole-of-government M&E system. These are the supply-side and the demand-side. In addition, there are known essentials deemed crucial to a successful whole-of-government M&E system. These include the political and technical issues associated with implementing country systems for M&E. Another essential is the ownership of M&E systems. Further, the paper also presents a comprehensive section showing the fundamental ten steps for building a functional whole-of-government M&E system. When these aspects are understood by governments and carefully institutionalised across structures, M&E would prove to be a useful tool to promote accountability, feedback and learning. It also goes without saying, that, in the absence of a stronger system for M&E, governments will most likely not tell success from failure, not see success and would fail to reward it. As such, governments would probably never recognize its failures, thus failing to correct it and ultimately fall short of demonstrating development results. Once these happen, such governments would not win public support.